2016
DOI: 10.1186/s12891-016-1212-7
|View full text |Cite
|
Sign up to set email alerts
|

Intra-session absolute and relative reliability of pressure pain thresholds in the low back region of vine-workers: effect of the number of trials

Abstract: BackgroundPressure pain thresholds (PPT) are commonly used to quantify mechanical pain sensitivity of deep structures. Excellent PPT reliability has been previously reported among the low back of healthy subjects. However, there is a lack of studies assessing PPT over the low back of workers exposed to biomechanical risk factors of low back pain. Thus, the purpose of this study was threefold: (1) to evaluate the intra-session absolute and relative reliability as well as minimal detectable change (MDC) values o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 56 publications
0
47
0
Order By: Relevance
“…The 95% confidence interval of the d was calculated as d ± t n−1 × √(SDd) 2 /n, where t n−1 corresponds to the value of t distribution with n−1 degrees of freedom, and n corresponds to the number of patients. 22 If the 95% confidence interval of the d did not include zero, the presence of fixed bias would be confirmed. We assessed the proportional bias by determining the linear regression between the averages and the differences of HBP values.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The 95% confidence interval of the d was calculated as d ± t n−1 × √(SDd) 2 /n, where t n−1 corresponds to the value of t distribution with n−1 degrees of freedom, and n corresponds to the number of patients. 22 If the 95% confidence interval of the d did not include zero, the presence of fixed bias would be confirmed. We assessed the proportional bias by determining the linear regression between the averages and the differences of HBP values.…”
Section: Discussionmentioning
confidence: 96%
“…We assessed the fixed bias by calculating the 95% confidence interval of the truenormaldfalse¯. The 95% confidence interval of the truenormaldfalse¯ was calculated as truenormaldfalse¯ ± t n−1 × √(SDd) 2 /n, where t n−1 corresponds to the value of t distribution with n−1 degrees of freedom, and n corresponds to the number of patients . If the 95% confidence interval of the truenormaldfalse¯ did not include zero, the presence of fixed bias would be confirmed.…”
Section: Methodsmentioning
confidence: 99%
“…The reported SEM and MDC in the present study are similar to what has been reported in other studies. Balaguier et al [19] tested PPT's in the low back region of vine-workers and reported a SEM ranged from 53.5 to 77.5 kPa and MDC ranged from 148.4 to 214.7 kPa (mean PPT = 459.5-516.0 kPa in trial 1 and mean PPT = 468.7-540.8 kPa in trial 2) between the first and second trials. Walton and colleagues [38] tested at the trapezius muscle and at tibialis anterior and obtained SEM ranged from 18.2 to 73.8 kPa and MDC ranged from 42.7 to 171.3 kPa (mean PPT = 251.8 kPa and 334.1 kPa).…”
Section: Discussionmentioning
confidence: 99%
“…Continuous and intense nociceptive input from a damaged joint may contribute to sensitization by enhanced pain responses, the spread of pain to larger body areas, and outside the symptomatic joint [8,13,14]. Previous studies have demonstrated PPT to have a high relative reliability in various anatomical locations like knee [15,16], neck [17,18], and lower back [19,20] both in patients and in healthy humans. However, the reliability of PPT is influenced by factors such as gender, age, investigator and [19,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation